Impact of aircraft systems within aircraft operation: A MEA trajectory optimisation study - Seresinhe, R. (Cranfield University, 2014)
Air transport has been a key component of the socio-economic globalisation. The ever increasing demand for air travel and air transport is a testament to the success of the aircraft. But this growing demand presents many challenges. One of which is the environmental impact due to aviation. The scope of the environmental impact of aircraft can be discussed from many viewpoints. This research focuses on the environmental impact due to aircraft operation. Aircraft operation causes many environmental penalties. The most obvious is the fossil fuel based fuel burn and the consequent greenhouse gas emissions. Aircraft operations directly contribute to the CO2 and NOX emissions among others. The dependency on a limited natural resource such as fossil fuel presents the case for fuel optimised operation. The by-products of burning fossil fuel some of which are considered pollutants and greenhouse gases, presents the case for emissions optimised operations. Moreover, when considering the local impact of aircraft operation, aircraft noise is recognised as a pollutant. Hence noise optimised aircraft operation needs to be considered with regards to local impacts. It is clear whichever the objective is, optimised operation is key to improving the efficiency of the aircraft. The operational penalties have many different contributors. The most obvious of which is the way an aircraft is flown. This covers the scope of aircraft trajectory and trajectory optimisation. However, the design of the aircraft contributes to the operational penalties as well. For example the more-electric aircraft is an improvement over the conventional aircraft in terms of overall efficiency. It has been proven by many studies that the more-electric concept is more fuel efficient than a comparable conventional aircraft. The classical approach to aircraft trajectory optimisation does not account for the fuel penalties caused due to airframe systems operation. Hence the classical approach cannot define a conventional aircraft from a more-electric aircraft. With the more-electric aircraft expected to be more fuel efficient it was clear that optimal operation for the two concepts would be different. This research presents a methodology that can be used to study optimised trajectories for more-electric aircraft. The study present preliminary evidence of the environmental impact due to airframe systems operation and establishes the basis for an enhanced approach to aircraft trajectory optimisation which include airframe system penalties within the optimisation loop. It then presents a suite of models, the individual modelling approaches and the validation to conduct the study. Finally the research presents analysis and comparisons between the classical approach where the aircraft has no penalty due to systems, the conventional aircraft and the more-electric aircraft. When the case studies were optimised for the minimum fuel burn operation, the conventional airframe systems accounted for a 16.6% increase in fuel burn for a short haul flight and 6.24% increase in fuel burn for a long haul flight. Compared to the conventional aircraft, the more electric aircraft had a 9.9% lower fuel burn in the short haul flight and 5.35% lower fuel burn in the long haul flight. However, the key result was that the optimised operation for the moreelectric aircraft was significantly different than the conventional aircraft. Hence this research contributes by presenting a methodology to bridge the gap between theoretical and real aircraft-applicable trajectory optimisation.